TMS and drugs revisited 2014. Issue 10 (October 2015) - Ziemann, Ulf; Reis, Janine; Schwenkreis, Peter; Rosanova, Mario; Strafella, Antonio; Badawy, Radwa; Müller-Dahlhaus, Florian
Highlights Pharmaco-TMS improved our understanding of the effects of TMS on the human brain. Pharmaco-TMS-EEG is a new research field to measure directly drug effects on brain excitability and connectivity. Pharmaco-TMS can monitor and possibly predict drug responses in neurological and psychiatric patients.